Recombinant Invasive Lactococcus lactis Carrying a DNA Vaccine Coding the Ag85A Antigen Increases INF-γ, IL-6, and TNF-α Cytokines after Intranasal Immunization - Mancha-Agresti, Pamela; de Castro, Camila Prosperi; dos Santos, Janete S. C.; Araujo, Maíra A.; Pereira, Vanessa B.; LeBlanc, Jean G.; Leclercq, Sophie Y.; Azevedo, Vasco (Frontiers in Microbiology, 2017)
Tuberculosis (TB) remains a major threat throughout the world and in 2015 it caused the death of 1.4 million people. The Bacillus Calmette-Guérin (BCG) is the only existing vaccine against this ancient disease; however, it does not provide complete protection in adults. New vaccines against TB are eminently a global priority. The use of bacteria as vehicles for delivery of vaccine plasmids is a promising vaccination strategy. In this study, we evaluated the use of, an engineered invasive Lactococcus lactis (expressing Fibronectin Binding Protein A from S. aureus) for the delivery of DNA plasmid to host cells, especially to the mucosal site as a new DNA vaccine against tuberculosis. One of the major antigens documented that offers protective responses against M. tuberculosis is the Ag85A. L. lactis FnBPA+ (pValac:Ag85A) which was obtained and used for intranasal immunization of C57BL/6 mice and the immune response profile was evaluated. In this study we observed that this strain was able to produce significant increases in the amount of pro-inflammatory cytokines (IFN-γ, TNF-α, and IL-6) in the stimulated spleen cell supernatants, showing a systemic T helper 1 (Th1) cell response. Antibody production (IgG and sIgA anti-Ag85A) was also significantly increased in bronchoalveolar lavage, as well as in the serum of mice. In summary, these findings open new perspectives in the area of mucosal DNA vaccine, against specific pathogens using a Lactic Acid Bacteria such as L. lactis